Repetative Transcranial Magnetic Stimulator (rTMS) Characterization and How to Develop the Functionalities for Treating Neural Disorders - Pirayeshfar, Amirsoheyl; Pakdaman, Hossein; Ghofrani, Mohammad Bagher; Roozbeh, Mehrdad; Gharagozli, Kourosh (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2022)
Background: Repetative transcranial magnetic stimulation (rTMS) is an important non-invasive technique with several protocols to treat a wide variety of neural disorders. This method utilizes a strong power supply to discharge high currents in a single or dual flat spiral coil with specific characterizations. It makes a magnetic field that promotes neuroplasticity by applying the field distribution on the appropriate brain zone and requires adjusting time and frequency relating to intervention protocols. Aim: This study investigates components of an rTMS machine to describe development approaches to increase performance, specifically in the binary mode of recovering proportionally with brain and heart signals. Methods: The proposed method achieves an rTMS and probe-set coil prototypes whose performance is approved with some statistical modelings and experiments analysis. Results: Results show that the physical properties of the coil are proportional to the power supply effect and the magnetic field distribution in front of the probe set. Conclusion: By clarifying the mechanism of oscillator switching modes and the location of the processing unit in rTMS, this paper is directed to utilize external sensors to create a smart stimulator with touch EEG or ECG signals through the most accurate intervention.